The Impact of Stress in Decision Making in the Context of Uncertainty - Morgado, Pedro (2015)
For a number of decades, different fields of knowledge, including psychology, economics, and neurosciences, have focused their research efforts on a better understanding of the decision-making process. Making decisions based on the probability of future events is routine in everyday life; it occurs whenever individuals select an option from several alternatives, each one associated with a specific value. Sometimes subjects decide knowing the precise outcomes of each option, but commonly they have to decide without knowing the consequences (because either ambiguity or risk is involved). Stress has a broad impact on animal behaviors, affects brain regions involved in decision-making processes, and, when maladaptive, is a trigger for neuropsychiatric disorders. This Mini-Review provides a comprehensive overview on how stress impacts decision-making processes, particularly under uncertain conditions. Understanding this can prove to be useful for intervention related to impairments to decision-making processes that present in several stress-triggered neuropsychiatric disorders.